Ten years of the Vienna Initiative 2009-2019 - European Investment Bank (European Investment Bank, 2019)
Amidst the global financial crisis, international institutions, national authorities and international commercial banks collaborated closely to prevent contagion spreading to Central, East and south east Europe. They built a platform, the Vienna Initiative, that helped curb disruptions and restore confidence in the banking system. Ten years later, the Vienna Initiative has transformed itself into a broader platform for collaboration. It tackles the unique challenges of a region that combines widespread cross-border banking with regulatory and supervisory interdependence, to better support innovation and growth. Commemorating 10 years of the Initiative, this book brings together experiences from the key actors and institutions involved from the beginning.
Description based on print version record.
KU Open Services
Keywords: Business & Economics / Economics; Economics; Electronic books